Knowledge, Attitude, And Practice of Pre-Clinic Dental Medicine Students on Oral Health Care - Vidyastami, Insyirah Dwi; Khadijah, Farahdiba; Rizqianti, Yuniar; Salsabila, Haidar Rosa; Fikriah, Kaifa Izatul; Kususmo, Aryo Dwipo (International Journal of Psychosocial Rehabilitation, 2020)
Background: Knowledge, attitude, and practice affect how a person maintains the health of the oral cavity. As dental medicine student, it is important to have a good knowledge of oral and dental hygiene and are expected to be able to give knowledge about oral health and could produce a change in attitude that being manifested in oral hygiene maintenance measures. Objective: To describe the knowledge, attitudes, and practice of Universitas Airlangga pre-clinic dental medicine students towards oral health care. Methods: This research was a descriptive quantitative study of Faculty of Dental Medicine Universitas Airlangga preclinical students. The sampling was cluster random sampling with a total of 96 people with observed variables, such as knowledge, attitudes, and behavior. Result: The level of attitude varies with the same high percentage of results in the batch 2016 and 2017 (45.8%), while in the batch 2018 it was 58.3% and in the batch 2019 79.2%. The level of behavior varies with high-yield dominated, in the batch 2016 and 2019 of 95.8% while in the batch 2017 and 2018 amounted to 91.7%. The level of attitude of female respondents had a higher yield of 58.1% compared to male respondents of 50%. Conclusion: The level of knowledge, attitudes, and behavior towards the oral health of Faculty of Dental Medicine Universitas Airlangga preclinical students was quite good and did not have a significant difference.